2001
DOI: 10.1603/0022-0493-94.2.339
|View full text |Cite
|
Sign up to set email alerts
|

Relative Effectiveness of Selected Stilbene Optical Brighteners as Enhancers of the Beet Armyworm (Lepidoptera: Noctuidae) Nuclear Polyhedrosis Virus

Abstract: The addition of a stilbene optical brightener, Tinopal LPW, at 1% concentration (wt:wt) significantly reduced the LC50 of the beet armyworm nuclear polyhedrosis virus (SeMNPV) from 2.9 PIB/mm2 to 0.02 PIB/mm2. Moreover, the LT50 of SeMNPV was reduced by 34% by the addition of Tinopal LPW. Seven other structurally related stilbene brighteners were also tested as viral enhancers. Five of these brighteners (Tinopal LPW, Blankophor BBH, Blankophor HRS, Blankophor P167, and Blankophor RKH) reduced LD50, whereas thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Reducing the LT 50 value as a result of adding FB to virus agrees with the finding by Shapiro and Robertson (1992), Adams et al, (1994), Zou andYoung (1996), Li and Otvos (1999 a & b), Shapiro and Hamm (1999), Shapiro (2000). Also, it was found in the present study that addition of 1% FB Wang and Granados (2000), Shapiro and Argauer (2001) and El-Salamouny (2004).to SpliNPV at LC 10 decreased larval weight of S. littoralis by 44.1%. This finding is in agreement with El-Salamouny et al, (2005) and El-Salamouny (2004), who reported that the reduction in larval weight was correlated with a high rate of enhancement effect.…”
Section: Discussionsupporting
confidence: 91%
“…Reducing the LT 50 value as a result of adding FB to virus agrees with the finding by Shapiro and Robertson (1992), Adams et al, (1994), Zou andYoung (1996), Li and Otvos (1999 a & b), Shapiro and Hamm (1999), Shapiro (2000). Also, it was found in the present study that addition of 1% FB Wang and Granados (2000), Shapiro and Argauer (2001) and El-Salamouny (2004).to SpliNPV at LC 10 decreased larval weight of S. littoralis by 44.1%. This finding is in agreement with El-Salamouny et al, (2005) and El-Salamouny (2004), who reported that the reduction in larval weight was correlated with a high rate of enhancement effect.…”
Section: Discussionsupporting
confidence: 91%
“…This synergistic effect had already been observed in L 1 and L 2 S. exigua (Hamm and Chandler 1996, Shapiro 2000, Shapiro and Argauer 2001 but no enhancement was detected for later instars (Zou and Young 1994). In other host-virus systems, such as those of P. includens (Zou and Young 1994) and L. dispar and their homologous NPVs (Shapiro and Robertson 1992), the addition of Tinopal LPW also enhanced NPV mortality in the late instars to a similar degree to that of early instars.…”
Section: Discussionmentioning
confidence: 79%
“…We also assessed any potential effect of Tinopal LPW on the genotypic composition of the virus after serial passage in vivo and quantiÞed the effects of the optical brightener on viral occlusion body production in L 2 and L 4 instars. We selected Tinopal LPW as this has proved to be among the most active optical brighteners for potentiation of the insecticidal capacity of baculoviruses (Hamm 1999, Shapiro andArgauer 2001).…”
mentioning
confidence: 99%
“…Following the discovery that stilbene optical brighteners act as virus enhancers (Hamm and Shapiro 1992;Shapiro and Robertson 1992;, studies were undertaken to determine structure-function relationships of sulfonic acid, triazine, and stilbene components of the stilbene optical brightener Tinopal LPW (Shapiro and Argauer 1997). Although none of the components tested acted as viral enhancers, the complete brightener (Tinopal LPW) enhanced the activity of the gypsy moth nucleopolyhedrovirus LdNPV (Shapiro and Argauer 1997). In a subsequent test, Argauer and Shapiro (1997) tested eight structurally similar stilbene optical brighteners.…”
Section: Discussionmentioning
confidence: 99%